Determining patient knowledge of direct oral anticoagulants: a questionnaire study. (1st April 2022) - Carey, M; Silvari, V; Crowley, E; McCarthy, S
Abstract: Introduction: There has been a significant increase in the number of patients prescribed Direct Oral Anticoagulants (DOACs) (1). One of the advantages of DOACs is reduced need for monitoring compared to warfarin, however less frequent contact with healthcare professionals (HCPs) may contribute to poor patient knowledge leading to negative health consequences. Aim: To determine patients' knowledge on DOACs in the hospital and community pharmacy setting. Methods: Participants were recruited from a university hospital and from a convenience sample of community pharmacies. Potential participants were identified by the pharmacist in that setting using the following criteria: age ≥18 years, adequate cognition, DOAC use ≥3 months. Following consent, the participant completed a questionnaire which consisted of participant demographics and questions from the KODOA (The Knowledge of Direct Oral Anticoagulants) questionnaire. Depending on participant preference, they either self-completed the questionnaire or provided oral answers which the researcher documented. Based on previous research (2), a target sample of 40 participants was set. Descriptive statistics were performed. Results: 40 participants were recruited; the mean (SD) age was 70.2 years (10.1), with 70% of participants reporting male gender. 62.5% of participants had an indication of atrial fibrillation. Mean (SD) duration of DOAC use was 5.6 years (3.6). Most patients rated their knowledge of their DOAC as moderate (50%) or good (27.5%). The results of the KODOA are presented in the table. The average score achieved by participant was 11.55/15 (± 1.88 SD). Participants scored high in areas such as DOAC indication, frequency of dosing, side-effects, drug interactions and when to seek further help. Areas of knowledge deficits included what to do when patients have forgotten a dose or have taken too much DOAC. Conclusion: One limitation of the questionnaire is that the questions are presented in a multiple-choice format and it is possible that participants may have selected the correct answer due to chance. However, overall, participants demonstrated good levels of knowledge of their DOAC therapy. This study has identified areas of knowledge deficits which could be included in patient education when HCPs are counselling patients, when starting their DOAC and continually throughout treatment. References: (1) Barry, Michael. Medicines Management Programme: Oral anticoagulants for stroke prevention in non-valvular atrial fibrillation [Internet]. 2019 [cited 2021 Jul 24]. Available from: https://www.hse.ie/eng/about/who/cspd/ncps/medicines-management/oral-anticoagulants/oral-anticoagulants-for-stroke-prevention-in-non-valvular-atrial-fibrillation-march-2019.pdf (2) Metaxas C, Albert V, Stahl M, Hersberger KE, Arnet I. Development and validation of a questionnaire to self-assess patient knowledge of direct oral anticoagulants (KODOA-test). Drug Healthc Patient Saf. 2018 Jul 20;10:69–77.